POLA KEBERAGAMAAN KAUM TUNA NETRA DAN DAMPAK PSIKOLOGIS TERHADAP PENERIMAAN DIRI - sulthon, Sulthon (Pascasarjana IAIN Kudus, 2016)
The diversity pattern of the blind community was influenced by various aspects and the diversity dimensions i.e. the dimensions of belief, the practice of worship (religious ritual), morals, full and total comprehension, and religious knowledge. The diversity pattern of the blind community in Kudus is vary widely depending on how much knowledge and understanding of religion, full and total comprehension towards his religion, the blind person attitude against his defect, the blind community in SDLB Purwosari Kudus generally have a strong diversity (good), and there was a (mediocre), and there are very less (abangan). The pattern of diversity of blind community has a very significant influence on the psychological and social development. The blind person who has a good (strong) diversity, it is supported by the strong religious knowledge and understanding will have a lightweight psychological development or not so heavy. Instead of a blind person who has less of religious knowledge and understanding will have an impact on the weight psychological and social development also. The pattern of diversity of blind community will have an effect on the psychological and social development and self-acceptance. The good pattern of diversity of blind community will bear a good religion full comprehension that further grow in self awareness and self acceptance that totality to the Almighty so that will bear good attitude and self-acceptance.